2016
DOI: 10.1016/j.ctrv.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives of sentinel lymph node dissection at the time of radical surgery for prostate cancer

Abstract: The sentinel lymph node dissection (SLND) concept relies on the accurate detection of primary nodal landing sites and could represent a major advancement towards accurate, non-invasive pelvic staging in prostate cancer (PCa). Different iterations of the technique have now been validated and reproduced mostly in large-volume centres. The existing evidence denotes the feasibility and sensitivity of SLND, with encouraging pre- and intraoperative detection rates of 98% and 96%. Yet, current surgical practice manda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
(235 reference statements)
0
10
0
Order By: Relevance
“…In a recent systematic review of SLN in PCa, the overall median pre-operative and intraoperative detection rates were 97.8 and 96.1%, respectively, with an overall median false negative rate of 7.1% (57).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…In a recent systematic review of SLN in PCa, the overall median pre-operative and intraoperative detection rates were 97.8 and 96.1%, respectively, with an overall median false negative rate of 7.1% (57).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The mean sensitivity and specificity for detecting LN metastasis in each pelvic lymphatic station were 67% and 90%, respectively. These findings indicate that as UBC metastasis to pelvic LNs is difficult to predict accurately using the SNB technique, it has low clinical value SLNs for prostate cancer (185). In other systemic review, van der Zaag et al, showed that the overall sensitivity rate of SN mapping in patients with colorectal cancer was 70% (186).…”
Section: Discussionmentioning
confidence: 99%
“…The use of tracer that only delineates lymphatic drainage transforms the procedure into a radio-guided or fluorescence-guided dissection (185). The future of a true SN concept seems to depend on the identification of a cancer-specific targeted ligand which is bound to an intraoperatively detectable tracer…”
Section: Detection Of Ln Metastasismentioning
confidence: 99%
“…[49][50][51][52][53] SLNs are the first station that receives lymphatic drainage from the primary tumor and reflects the status of other DLNs. [57] The SLN biopsy with the gold standard method is not much in clinical settings due to the use of radiotracer, and novel radioisotope-free methods are expected. Traditional LN mapping techniques in clinical applications include radionuclide, blue dyes, and fluorescence imaging.…”
Section: Mapping Sentinel Lymph Nodes (Slns) For Surgerymentioning
confidence: 99%